축산물 수급과 유통 - 유철호 (한국농촌경제연구원, 2004)
This volume is prepared as an overview reference literature regarding the balance situations of 'livestock products'(beef, pork, dairy milk, broiler meat and eggs) and domestic marketings of those products produced in Korea. Specifically, relevant topics are arranged as follows. The first chapter delineates changes occurred in the various factors which had affects on the balances of major livestock products(beef, pork, dairy milk, broiler meat and eggs) and the marketing of those products over the period of 1960-2001. They include number of households, household income, expenditure on the those products, the proportions of intakes from those products to the total three basic nutritional intakes(carbon hydrate, protein and fat) from diet. The chapter also includes an overview of Korean livestock sector over the period: gross money values of the products produced, yearly stock of animals and production cost of the individual products. The chapters following the first chapter up to chapter four are devoted to the specifics on marketings of individual products: two major meats(beef and pork in chapter two), broiler meat and eggs(chapter three) and dairy milk(chapter four) based on a surveyed data in 2002. The specifics include marketing channels through which the individual products flow with proportions going through individual routes from farmgate to consumer, and breakdown of marketing costs incurred with the flow(except for dairy milk). These chapters also show graphic charts of price spreads among the marketing stages(farmgate, wholesale and retail) for meats of various kinds and eggs over the period of 1960-2002 on individual product basis. Also included in these chapters are overviews on a fast-phased revamping of some physical marketing facilities undergone and changes in the noteworthy institutional arrangements in the marketing of livestock products over the period. Chapter five delineates changes in the proportions of domestic supplies of the individual livestock products to the total consumption with imports of livestock products and other related issues including domestic distributions of individual products around the period when the individual product markets were liberalized in the 1990s. Emphasis is placed on the imports of beef and domestic distribution of the product, along with related marketing arrangements for the product before the beef market liberalization in 2001. Chapter six examines selected government policies, related to the marketing of the livestock products, which have been implemented since the early 1990s. They include abolition of government control on the retail prices of beef and pork, adoption of carcass grading system for meats(beef and pork) and establishment of large scale meat processing facilities around the country. The last chapter overviews prospects of overall future balances of livestock products and the effects of government policies implemented for the improvement of marketing of livestock products and points out several policy measures to be further pursued for the future. They include measures for further enhancing the quality of domestic products and the level of food safety, increased transparency in all stages of marketing of the products in order to protect end-users as well as domestic producers of the products, and increased role of producers' organization in marketing of the products. Among others, the task for increased transparency in the marketing needs to have a continued attention and priority with recent increased incidences of fraudulent practices of cross-selling of low priced imported products as high priced domestic products.